Soil physical properties and land use and land cover as a basis for understanding linear erosive processes in the hydrographic basin of the Cachorros river, Amazônia Maranhense - Fushimi, Melina; Oliveira, Regina Célia de [UNESP]; Nunes, João Osvaldo Rodrigues [UNESP] (Universidade Federal de Goias, 2023)
The current work analyzed the correlation between soil physical properties and land use and land cover as a basis for understanding linear erosive processes in the hydrographic basin of the Cachorros river, Amazônia Maranhense. The materials and methods included a general description, morphological and textural analysis of soils and sand fraction, through fieldwork and laboratory analysis, as well as mappings, with the elaboration of the outline of the main soil classes and the land use and land cover map. The results showed that in the soil profiles A and B the textural classes “Loamy sand” and “Sandy loam” predominate, being naturally fragile to erosion, where the sand fraction prevails in all horizons. The physical attributes structure, consistency and porosity are directly influenced by land use and their interrelations accelerate linear erosive dynamics by rills and ravines, with the possibility of evolution to gullies.
Propiedades físicas del suelo y cobertura y uso de la tierra como subsidio a la comprensión de los procesos erosivos lineares en la cuenca hidrográfica del rio de los Cachorros, Amazônia Maranhense
Propriedades físicas do solo e cobertura e uso da terra como subsídio à compreensão dos processos erosivos lineares na bacia hidrográfica do rio dos Cachorros, Amazônia Maranhense
Keywords: Mineral extraction; Ravines; Rills; Vegetation